The girl who saved Yesterday - Lester, Julius; Angel, Carl ([Berkeley, California] : Creston Books, LLC, 2016)
Silence, sent on a mysterious mission by the ancient trees that raised her after she was sent away from her village, reconnects the villagers with their forgotten ancestors.
Kirkus Starred, March 2016
5.6
K-3
Keywords: Villages -- Fiction; Generations -- Fiction; Trees -- Fiction; Africa -- Fiction; Villages -- Fiction; Age -- Fiction; Trees -- Fiction; Africa -- Fiction